2021
DOI: 10.30993/tifbr.v15i2.285
|View full text |Cite
|
Sign up to set email alerts
|

Do Financing Schemes Affect the Functions of Islamic Banks in Indonesia?

Abstract: This study aims to examine the effect of financing schemes on the dual functions of Islamic banks. For intermediary function, its analysis the financing schemes toward profitability. Financing schemes consist of Mudharabah, Qardh, Istisna’ and Ijarah. Meanwhile, the profitability level is measured by Return on Asset (ROA). In this study, the authors used the data from Financial Services Authority (OJK) for the study period from 2014 till 2022. This research used the Multiple Linear Regression to analyze the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…However, this result does not support research by Yusuf et al. (2019) and Suwasdi et al. (2021), which found that PLS financing has not significantly affected the ROA of Islamic Banks, which means PLS financing does not increase the level of profitability of Islamic Banks.…”
Section: The Effect Of Pls (Mudharabah and Musyarakah) Financing On P...contrasting
confidence: 86%
See 2 more Smart Citations
“…However, this result does not support research by Yusuf et al. (2019) and Suwasdi et al. (2021), which found that PLS financing has not significantly affected the ROA of Islamic Banks, which means PLS financing does not increase the level of profitability of Islamic Banks.…”
Section: The Effect Of Pls (Mudharabah and Musyarakah) Financing On P...contrasting
confidence: 86%
“…The greater the PLS financing, the greater the profits obtained by the Bank (Kuswara et al 2019;Masnah & Hendrawati, 2020). However, different results were found by Yusuf, Hamdani, & Kholik (2019) and Suwasdi, Hidayah & Nasution (2021), where PLS financing hurts the profitability of Islamic banks, meaning that mudharabah and musyarakah financing decreases the level of profitability. Therefore, the hypothesis to be tested in this study is: H1: PLS financing has a positive and significant effect on the profitability of Islamic Rural Bank in Indonesia.…”
Section: Hypothesismentioning
confidence: 80%
See 1 more Smart Citation
“…Without education, humans will find it difficult to keep up with the rapid advancements in knowledge. Education is expected to build high-quality and highly competitive individuals, and it is also expected to humanize people through education, in line with Nelson Mandela's statement that education is the only thing that can change the world (Suwasdi & Said, 2022).…”
Section: Introductionmentioning
confidence: 80%
“…Universities can play an active role in helping zakat management organizations identify potential beneficiaries requiring financial assistance for education (Kopnina, 2020). This creates a synergy between the world of education and social empowerment, which in turn can increase the effectiveness of university management in making a positive contribution to society through quality and inclusive education (Suwasdi & Said, 2022). Thus, the close relationship between zakat management organizations and universities can create an ecosystem that supports education and social welfare (Alshater et al, 2021;Rahim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%